Serum Calcium as a Preoperative Surrogate of Tumour Burden in Stage III Breast Carcinoma: A Cross-Sectional Surgical-Oncology Study - Feizal Faturahman; Mulawan Umar; Theodorus (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2026)
Introduction: Stage III breast carcinoma dominates surgical-oncology practice in Indonesian referral hospitals. Tumour-secreted PTHrP and dysregulated calcium signalling link tumour mass to systemic calcium, yet routinely available serum calcium is rarely quantified as a preoperative surrogate of tumour burden. Methods: In this cross-sectional study, 35 women with Stage III breast carcinoma at Dr. Mohammad Hoesin General Hospital Palembang underwent preoperative serum calcium measurement. Tumour size was dichotomised (≤5 cm vs >5 cm). Associations were tested by Spearman correlation and the Mann–Whitney U test; serum calcium was assessed as a classifier of large tumours by ROC analysis, with multivariable logistic regression, effect sizes and 95% confidence intervals (CI). Results: Mean serum calcium was 9.34 ± 0.82 mg/dL, and 27 patients (77.1%) had tumours >5 cm. Calcium was higher in tumours >5 cm (9.58 ± 0.76 mg/dL; 95% CI 9.28–9.88) than ≤5 cm (8.54 ± 0.37 mg/dL; 95% CI 8.23–8.85), a difference of 1.04 mg/dL (95% CI 0.66–1.43; Cohen d = 1.50; Mann–Whitney U = 0.000; p < 0.001; r = 0.72). Calcium correlated with size (Spearman rho = 0.731; p < 0.001) and discriminated tumours >5 cm (area under the curve 1.000; cut-off 8.95 mg/dL; sensitivity and specificity 100%). Immunohistochemical subtype was the only independent predictor (adjusted odds ratio 71.37; 95% CI 2.95–1728; p = 0.009). Conclusion: Preoperative serum calcium rose in proportion to tumour size in Stage III breast carcinoma, acting as a low-cost surrogate of tumour burden that may aid risk stratification in resource-limited centres, pending validation.